Evaluation of treatability of high strength wastewater in a three stage-rotating biological contactor - Ebrahimi, Atieh; Najafpour, Ghasem D.; Nikzad, Manouchehr (Journal of Environmental Engineering and Landscape Management, 2017)
Cheese whey effluent contains biodegradable organic compounds in the range of 40 to 80 g. L–1. In this study, a three–stage rotating biological contactor was fabricated as a bench scale experimental unit to remove organic matters from cheese whey. First, the treatability of cheese whey effluent in the three–stage rotating biological contactor (RBC) was evaluated. Then the effect of extended specific surface area (SSA) and recirculation rate on COD removal was investigated. The obtained results showed that the organic removal rate increased with an increase in loading rate, till other limiting parameters affect the process. Prior to application of the designated modifications to the system, maximum COD removal efficiency at hrts of 24 and 36 h with OLR of 50 gcod.L–1.d–1 was 90 and 92.4%, respectively. The removal efficiency was improved as a result of increasing the SSA and recirculation rate. Also, recirculation rate may assist to increase the DO level of the wastewater, especially at high olrs. To sum up, obtained results showed that whey effluent has been efficiently treated in a continuous operation of bench scale RBC.First published online: 26 Jun 2017